2016
DOI: 10.1007/s11936-016-0440-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Management of Concomitant Hypertrophic Obstructive Cardiomyopathy and Valvular Aortic Stenosis

Abstract: The dilemma of the patient with both AS and LVOTO is now commonly encountered in clinical practice; indeed, physicians must be aware of the complex interaction and coexistent nature of both diseases, especially as both HOCM and TAVR have increased in awareness and prevalence. Importantly, the clinician must be aware of the complex interplay hemodynamically, with the two diseases confusing the TTE imaging and potentially affecting each other anatomically and clinically. There is no set guideline on how to appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Its utility in patients with serial obstructions related to HCM and AS is unclear. 6 In this case series, we describe the hemodynamic and early clinical outcomes of six patients with echocardiographic and hemodynamic findings suggestive of dynamic LVOT obstruction and fixed AS obstruction. We found that septal ablation in this setting was well tolerated and associated with a significant immediate reduction in the dynamic LVOT gradient with residual fixed gradient associated with AS.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Its utility in patients with serial obstructions related to HCM and AS is unclear. 6 In this case series, we describe the hemodynamic and early clinical outcomes of six patients with echocardiographic and hemodynamic findings suggestive of dynamic LVOT obstruction and fixed AS obstruction. We found that septal ablation in this setting was well tolerated and associated with a significant immediate reduction in the dynamic LVOT gradient with residual fixed gradient associated with AS.…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol septal ablation is an established treatment modality to relieve dynamic LVOT obstruction in patients with symptoms refractory to medical therapy deemed to be high‐risk for surgery. Its utility in patients with serial obstructions related to HCM and AS is unclear . In this case series, we describe the hemodynamic and early clinical outcomes of six patients with echocardiographic and hemodynamic findings suggestive of dynamic LVOT obstruction and fixed AS obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations